Genome sequence of a commensal bacterium, Enterococcus faecalis CBA7120, isolated from a Korean fecal sample. Issue 1 (December 2016) - Kim, Joon; Song, Hye; Kim, Yeon; Kwon, Joseph; Choi, Jong-Soon; Cho, Yong-Joon; Kim, Byung-Yong; Rhee, Jin-Kyu; Myoung, Jinjong; Nam, Young-Do; Roh, Seong
Abstract Background Enterococcus faecalis, the type strain of the genusEnterococcus, is not only a commensal bacterium in the gastrointestinal tract in vertebrates and invertebrates, but also causes serious disease as an opportunistic pathogen. To date, genome sequences have been published for over four hundredE. faecalis strains; however, pathogenicity of these microbes remains complicated. To increase our knowledge ofE. faecalis virulence factors, we isolated strain CBA7120 from the feces of an 81-year-old female from the Republic of Korea and performed a comparative genomic analysis. Results The genome sequence ofE. faecalis CBA7120 is 3, 134, 087 bp in length, with a G + C content of 37.35 mol%, and is comprised of four contigs with an N50 value of 2, 922, 046 bp. The genome showed high similarity with other strains ofE. faecalis, including OG1RF, T13, 12107 and T20, based on OrthoANI values. Strain CBA7120 contains 374 pan-genome orthologous groups (POGs) as singletons, including "Phages, Prophages, Transposable elements, Plasmids, " "Carbohydrates, " "DNA metabolism, " and "Virulence, Disease and Defense" subsystems. Genes related to multidrug resistance efflux pumps were annotated in the genome. Conclusions The comparative genomic analysis ofE. faecalis strains presented in this study was performed using a variety of analysis methods and will facilitate future identification of hypothetical proteins.